Influence of social conditions and ideological upbringing on the education of soviet pedagogical institute students in the 1960s - Smirnitsky, Alexander Evgenievich; Smirnitsky, Nina Vladimirovna; Shurshikova, Anna Vladimirovna; Shlyakhov, Mikhail Yurievich; Nochvina, Bella Anatolyevna (Nuances: Estudos sobre Educação, 2021)
The study is carried out within the framework of the developing trend in Russian historical science—the history of everyday life. Particular attention is paid to the study of various organizational forms of life of the Soviet student community in a provincial town, as Gorky was at that time, during a difficult and intense period in both domestic and foreign policy in the history of the USSR. The authors use the local method of historical research, showing the history of the country through the prism of the history of a particular locus. Materials of the periodical press devoted to student life and the most troubling problems of students are involved in the study. The novelty of the article lies in the introduction of several previously unpublished sources shedding light on some aspects of the life of the student community, combining the local method with the history of everyday life.